ARCHAEOLOGY OCROS DISTRICT: SETTLEMENTS OF LATE INTERMEDIATE PERIOD IN QAQAMARCA MICROCUENCA RIVER , CHUMBES VALLEY - AYACUCHO. - García Reyes, Anuor Abel (2015)
This article discusses the results of archaeological survey work conducted in the watershed of Qaqamarca River - Valley Chumbes, Ocros district, Huamanga in 2008, as part of the course of pre-professional practices. The data presented below relate to settlements of the Late Intermediate Period (Chanca), whose cultural traditions reveal an established technological knowledge and therefore, we are faced with a very complex culture. Its architectural pattern reflects a circular arrangement bonded associated with individual and collective burial ground, and defensive systems; the found ceramic pottery is related to Chanca. In short, the study of the cultural traditions of this period is complex, and therefore, the present study provides a contribution more about Chanca occupation in the lower basin of the Pampas river.